Prosodic Variation in Academic Public Presentations - Elena Freydina (National Research University Higher School of Economics, 2015)
The article reports on a study of the prosodic characteristics of academic public presentations. Prosodic variation is analysed with regard to the social and cultural context which is significant for the adequate description of discourse prosody. The paper draws on the findings made in the course of the analysis (auditory and acoustic) of presentations delivered by British lecturers. The article contains an overview of contextual factors and discourse strategies used in academic presentations. Special focus is given to prosodic variations in spoken discourse determined by the extralinguistic context. The author argues that that the choice of prosodic means depends on a variety of contextual parameters: speaker-audience relationships (reflected in the tenor of discourse), the speaker's rhetorical competence, method of delivery, rhetorical tradition and others. The observations made in the paper may be useful to develop expertise in the delivery of academic public presentations which is an important aspect of EFL teachers' professional training.